2013
DOI: 10.2136/vzj2012.0150
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fate and Transport in a Conventional Onsite Wastewater Treatment System Installed in a Clay Soil: A Nitrogen Chain Model

Abstract: Nitrogen cycling in clay‐textured soils with onsite wastewater treatment systems (OWTS) is studied and modeled much less often than sand‐ and loam‐textured soils because there is little data on OWTS performance in these soils. Information on the nitrogen loads from these systems is needed for quantification of total maximum daily loads (TMDLs). The objective of this study was to calibrate a 2D HYDRUS model using experimental soil pressure head and vadose zone nitrogen (N) and chloride (Cl) data from a conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 19 publications
2
17
1
Order By: Relevance
“…The fitted value indicates that denitrification occurs when water contents rise above 42% of the value for field capacity. This threshold is <60% of the relative water content reported by Bradshaw et al (2013) and Beggs et al (2004) in OWTS drain fields. However, Schepers and Raun (2008) reported that denitrification can start in 20% water-filled pore space and increases with an increasing percentage of water-filled capacity, depending on the availability of C and NO 3 .…”
Section: Aquifer As Presented Inmentioning
confidence: 64%
“…The fitted value indicates that denitrification occurs when water contents rise above 42% of the value for field capacity. This threshold is <60% of the relative water content reported by Bradshaw et al (2013) and Beggs et al (2004) in OWTS drain fields. However, Schepers and Raun (2008) reported that denitrification can start in 20% water-filled pore space and increases with an increasing percentage of water-filled capacity, depending on the availability of C and NO 3 .…”
Section: Aquifer As Presented Inmentioning
confidence: 64%
“…The model included the nitrification of NH 4 -N and PMN to NO 3 -N as well as denitrification from NO 3 -N to dinitrogen/ nitrous oxide (N 2 /N 2 O). The intermediate product of nitrification, NO 2 -N, was ignored to simplify the chain model (Bradshaw et al 2013). The first-order reaction rates for the change in NH 4 -N + PMN (equation 6) and NO 3 -N (equation 7) concentrations that result from the N chain models were…”
Section: Methodsmentioning
confidence: 99%
“…Complete denitrification of NO 3 -N was assumed to occur under saturated conditions, and rate constants were set the same as for nitrification (table 2). Adsorption coefficients for NH 4 -N/PMN and NO 3 -N were 10 and 0.78 cm 3 g -1 for all soil horizons (table 2), and were based on values from Bradshaw et al (2013). Based on R 2 in model output, the adsorption coefficient was optimized across models using manual calibration to provide a more acceptable fit to observed NO 3 -N concentrations at the 8 and 75 cm depths.…”
Section: Soil Layer Particle Fraction (%) (Cm)mentioning
confidence: 99%
See 1 more Smart Citation
“…The production of these gases during nitrification and denitrification is influenced by the concentration and diffusion rate of O 2 in the soil (Bollmann and Conrad, 1998; Zhu et al, 2013; Peng et al, 2014; Medinets et al, 2015). As it is difficult to measure O 2 in the soil, soil moisture content is often used as a proxy for both O 2 concentration and diffusion rate (Bradshaw et al, 2013b; Geza et al, 2014). Beggs et al (2011) observed that nitrification rates increased linearly at 10 to 15% volumetric water content (VWC) and decreased at 26 to 45% VWC.…”
mentioning
confidence: 99%